New species, redescriptions, and new records on Mexican and Central American Cerambycidae (Coleoptera) - Heffern, Daniel; Santos-Silva, Antonio; Nascimento, Francisco E. De L. (Zootaxa, 2018)
Three new species are described: Compsibidion vandenberghei (Cerambycinae, Neoibidionini), from Nicaragua; Heterachthes zapopana (Cerambycinae, Neoibidionini), from Mexico; and Phaea lingafelteri (Lamiinae, Tetraopini), from Nicaragua. Phaea beierli Chemsak, 1999, and P. kellyae Chemsak, 1999 are redescribed. Pirangoclytus latithorax (Martins & Galileo, 2008) (Cerambycinae, Clytini), and Euryestola cribrata (Bates, 1881) (Lamiinae, Calliini) are newly recorded for Nicaragua.